Avoidant attachment style predicts less positive evaluations of warm (but not cold) social groups. (January 2018) - Santascoy, Nicholas; Burke, Sara E.; Dovidio, John F.
Two studies investigated the hypothesis that because individuals who are high on attachment avoidance tend to be disinterested in warmth in interpersonal relationships, they may respond less favorably to groups perceived as warm, attenuating the generally positive association between perceived warmth and favorable evaluation of a group. In Study 1, participants responded to groups representing the four quadrants based on warmth and competence identified by the stereotype content model (e.g., White people, homeless people). On average, people evaluated groups higher in stereotypical warmth more positively. However, as predicted, this effect was significantly weaker among participants higher in attachment avoidance. No effect was found for attachment anxiety. Study 2, in which the perceived warmth of a fictitious group was experimentally manipulated, conceptually replicated the effect for attachment avoidance. Understanding how attachment avoidance may attenuate favorable attitudes toward socially warm groups can help illuminate broader processes of intergroup relations.